UPAYA PENINGKATAN KEMAMPUAN GURU SMA DALAM MELAKSANAKAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI SEKOLAH BINAAN KABUPATEN BANGKALAN - Atik Sulistiatik (re-JIEM (Research Journal of Islamic Education Management), 2019)
The ability of teachers to prepare learning plans as a reference for implementing learning is not all good. In this regard, this study aims to improve the ability of teachers to carry out learning that refers to learning plans that are measured using instruments. the research method used school action assessment through two cycles. Cycle one includes planning, implementation, observation and reflection. From one cycle that has not been fulfilled, followed by the second cycle action. The research subjects were the high school teachers of the target schools in the Bangkalan District. Data collection techniques are descriptive. The indicator of success is if the value of each component is good, the value is at least 80 from a maximum value of 100. Learning planning has a minimum value of 28 from a maximum score of 35. The assessment in cycle one has not reached standard because the value is below 80 for learning and learning plan still under 28. Assessment in the second cycle of achievement of the implementation of learning between 80 to 84 while for planning learning between 28 to 34. Keywords: teacher ability, implementation of academic supervision learning